2016
DOI: 10.1037/xlm0000243
|View full text |Cite
|
Sign up to set email alerts
|

A general valence asymmetry in similarity: Good is more alike than bad.

Abstract: The density hypothesis (Unkelbach, Fiedler, Bayer, Stegmüller, & Danner, 2008) claims a general higher similarity of positive information to other positive information compared with the similarity of negative information to other negative information. This similarity asymmetry might explain valence asymmetries on all levels of cognitive processing. The available empirical evidence for this general valence asymmetry in similarity suffers from a lack of direct tests, low representativeness, and possible confound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 110 publications
7
86
0
Order By: Relevance
“…The angles between likeability and competence indicate a high positive correlation (24°at high pole, 35°at low pole). This density effect has been previously generalized across hundreds of positive and negative words, images and daily events (Koch, Alves, Kr€ uger, & Unkelbach, 2016), and agrees with findings by Bruckm€ uller and Abele (2013) showing that the positive poles of the Big Two (i.e., communion and agency dimensions) are perceived as more similar than their negative poles. We further examined how these differences in the relationship with valence played a role in the negative correlation found between the Dominant and Competent judgments.…”
Section: Property Fittingsupporting
confidence: 90%
“…The angles between likeability and competence indicate a high positive correlation (24°at high pole, 35°at low pole). This density effect has been previously generalized across hundreds of positive and negative words, images and daily events (Koch, Alves, Kr€ uger, & Unkelbach, 2016), and agrees with findings by Bruckm€ uller and Abele (2013) showing that the positive poles of the Big Two (i.e., communion and agency dimensions) are perceived as more similar than their negative poles. We further examined how these differences in the relationship with valence played a role in the negative correlation found between the Dominant and Competent judgments.…”
Section: Property Fittingsupporting
confidence: 90%
“…We have discussed theoretical reasons for these phenomena elsewhere (Sylvester et al, 2016; cf. Ashby and Isen, 1999; Koch et al, 2016) and will not go into details here. For the present purposes, however, two points are important: first, negative stimuli are usually more arousing than positive ones, and, second, positive ones typically are processed faster.…”
Section: Methods and Materials For Measuring Eadsmentioning
confidence: 99%
“…The authors interpreted this bias in terms of the above discussed asymmetry in semantic representations of negative vs. positive words: negative words are less homogenous, i.e., have less elaborated and cohesive representations (Ashby and Isen, 1999; Koch et al, 2016; Sylvester et al, 2016). Lüdtke and Jacobs (2015) therefore assumed that semantic integration and coherent situation model building for sentences with two negative words could be harder compared to sentences with two positive words.…”
Section: Multiword Expressionsmentioning
confidence: 99%
“…Comparing the effects of trait/behavior valence (positive vs. negative) to the effects of trait/behavior dimension (agency vs. communion) also contributes to a better understanding of halo effects in general. Gräf and Unkelbach () showed that valence influences the processes (and thus the strength) of halo effects, presumably mediated by trait density/similarity (Koch, Alves, et al, ; Unkelbach, ; Unkelbach et al, ). In contrast, the comparison of agency vs. communion apparently only affected the strength (i.e., halo effects from communion traits/behaviors were stronger than halo effects from agency traits/behaviors), but not the processes of halo effects.…”
Section: Discussionmentioning
confidence: 99%
“…They based their predictions on the differential similarity of positive information and negative information. Positive information is on average more similar to other positive information, and negative information is on average more distinct from other negative information (Koch, Alves, Krüger, & Unkelbach, ; Unkelbach, ; Unkelbach, Fiedler, Bayer, Stegmüller, & Danner, ). They predicted and found that negative halo effects (sometimes called horn effects ) occur directly by inferences from one salient trait to another.…”
Section: Explaining Halo Effectsmentioning
confidence: 99%